Assessment of sewerage system and impacts of wastewater on the environment and reusing in Erbil city - Shuokr Qarani Aziz; Jwan Sabah Mustafa; Bruska Sardar Mamand; Anwer Hazim Dawood; Sazan Mohammed Ali; Zana Aziz Mohammed Ameen (Reciklaža i Održivi Razvoj)
This study provides a comprehensive assessment of the sewage system in the city of Erbil, Iraq, focusing on the wastewater's quality, quantity, and the environmental impact of untreated wastewater disposal. The city does not have a centralized wastewater treatment plant, although a design has already been approved. The study evaluates the current system by comparing existing data with previous research and highlighting the impact of lifestyle on wastewater characteristics in the region. The study highlights the dangers of reusing untreated wastewater for irrigation, which poses significant health and environmental risks, including groundwater contamination. Data was collected through site visits to various locations in the city of Erbil. The research discussed the current and potential impacts of wastewater on watercourses. It was found that the majority of wastewater in Erbil is discharged untreated into the environment, causing significant pollution problems. The total amount of produced wastewater and irrigated area is 257,184 m3/day and 5,143,680 m2/day respectively. In addition, the study concluded with recommendations for treatment processes suitable for the specific types of wastewater in Erbil. It emphasizes the importance of establishing a wastewater treatment plant to protect the environment in the area.